ONLINE TIKET WEEK, STRATEGI PEMASARAN UNTUK MENINGKATKAN ANTUSIASME PELANGGAN TIKET.COM - Nurshal Shabila Mantika; Anisatul Auliya; Diani Mustika Prianti (Fakultas Pariwisata Universitas Pancasila, 2022)
Industry 4.0 is a revolution with exponential speed. In addition, Industry 4.0 enables billions of people to connect and access unlimited knowledge with mobile devices with unprecedented computing power and storage capacity. This study aims to explain and describe the marketing strategy of the